Identification of water logging tolerant Maize (Zea mays L.) landraces from Northeast India - Debbarma, Kunaljit; Sen, Devyani (Umiam : CPGS, CAU, 2014)
A set 60 maize landraces were screened under excess moisture condition to identify tolerant genotypes. Excess soil moisture stress conditions were imposed by continuous flooding of the field for 10 days at a depth of 10.0 ± 0.5 cm at the critical growth stages of maize viz. V2 (early vegetative stage), V7 (Knee-high stage) and VT (Tasseling stage). Several morpho - physiological parameters were recorded and path coefficient correlation was calculated for direct and indirect contribution of different variables with respect to yield under water logged conditions. Partitioning the correlation coefficient into cause and effect revealed that direct selection for cob weight which had a highly significant correlation with yield, would prove effective in improving yield. Additional parameters like anthesis silking interval (ASI), cob length and plant height also had significant correlation with yield. Further, a set of ten tolerant maize landraces were selected for screening at seedling stage. Selection was done on the basis of a low crop susceptibility index for yield and their ability to form brace roots under stress. Cup screening involved subjecting the seedlings to continuous water logging conditions for 25 days. Chlorophyll content was recorded lower in treated plants, the formation of adventitious roots as a response to water logging was significantly higher in the treated seedlings. The shoot to root weight ratio was also found higher in treated seedlings. Significant differences for formation aerenchyma in the mid cortex region of the roots under excess moisture condition was noticed in the water logged treatments. Increase in number of adventitious roots and formation of lysigenous aerenchyma are indicators of the plants ability to effectively withstand prolonged water logging. Landraces given the alphanumeric code S16 and Ma 5 were ranked the best performers both in field and green house conditions and can be further exploited for breeding for water logging stress.
Keywords: Maize -- Excess moisture tolerant